2012
DOI: 10.1039/c2jm16161c
|View full text |Cite
|
Sign up to set email alerts
|

A template-free synthesis and structural characterization of hierarchically nano-structured lithium-titanium-oxide films

Abstract: A template-free sol-gel method for the synthesis of hierarchically nano-structured lithium-titaniumoxide films is proposed involving a p-type doping of titanium isopropoxide sols with lithium. The structures of the films are analyzed by scanning electron microscopy, X-ray powder diffraction and Raman spectroscopy. Different phases can be accessed by controlling the annealing temperature. Supersaturated anatase (Ti, Li)O 2 is formed at 400 C, whereas anatase and/or rutile interspersed with Li 2 TiO 3 and Li 4 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Small amount of this Li2TiO3 impurity is often observed in Li4Ti5O12 powders synthesized by different techniques such as solid state 14 or sol gel methods 15,16 . Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Small amount of this Li2TiO3 impurity is often observed in Li4Ti5O12 powders synthesized by different techniques such as solid state 14 or sol gel methods 15,16 . Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The higher frequency band at 675 cm À1 was assigned to vibrations of Ti-O stretching vibrations in TiO 6 octahedra whereas the 420 and 340 cm À1 Raman lines were assigned to the stretching vibrations of the Li-O bonds in LiO 4 and LiO 6 polyhedra, respectively [40][41][42]. The Raman bands below 300 cm À1 were attributed to the bending vibrations of O-Li-O bonds (225 cm À1 ) and O-Ti-O bonds (272 cm À1 ) [43,44]. Julien et al [40] reported also the Raman spectra of Li 4 Ti 5 O 12 that was found to display bands at 671,430, 347, 271, and 232 cm À1 which were tentatively assigned to the five expected A1 g, F2 g, and Eg symmetry species for the spinel Oh 7 spectroscopic point symmetry group.…”
Section: Resultsmentioning
confidence: 99%
“…In such conditions, the hydrolyzed titanium species can condense into small oligomeric units [20], which could be responsible for the imperfect cationic homogeneity in the dip coated film. It should however be emphasized that the films studied here have a better homogeneity than usually encountered in sol-gel syntheses of lithium titanate, where strong reflections of TiO 2 anatase appear first and lithium titanate is formed only at higher temperatures (see [29] for a recent example).…”
Section: Inorganic Networkmentioning
confidence: 99%